Species-specific responses of foliar nutrients to long-term nitrogen and phosphorus additions in a lowland tropical forest - Mayor, Jordan R.; Wright, S. Joseph; Turner, Benjamin L. (The Journal of ecology, 2014)
1. The concentration, stoichiometry and resorption of nitrogen (N) and phosphorus (P) in plant leaves are often used as proxies of the availability of these growth-limiting nutrients, but the responses of these metrics to changes in nutrient availability remain largely untested for tropical forest trees. 2. We evaluated changes in N and P concentrations, N/P ratios and resorption for four common tree species after 13 years of factorial N and P additions in a lowland tropical forest in Panama. 3. Chronic P addition increased foliar P concentrations, decreased P resorption proficiency and decreased N/P ratios in three locally common eudicot tree species (Alseis blackiana, Heisteria concinna, Tetragastris panamensis). The increase in foliar P involved similar proportional increases in organic and inorganic P in two species and a disproportionately large increase in inorganic P in A. blackiana. 4. Nitrogen addition did not alter foliar N concentrations in any species, but did decrease N resorption proficiency in H. concinna. 5. A fourth species, the palm Oenocarpus mapora, demonstrated remarkably static foliar nutrient concentrations, responding only with a marginal decrease in P resorption proficiency under N plus P co-addition. 6. Synthesis. Collectively, these results suggest that adjustment of N/P ratios can be expected in eudicots exposed to elevated P, but foliar N appears to already be at optimal levels in these lowland rain forest tree species. The complexity of species-specific responses to altered nutrient availability highlights the difficulty in predicting future responses of tropical forest trees to a changing world.